The Effects of Halal Food Socialization by the Culture and Tourism Office of South Sulawesi to the Increase of Tourists Visit in the City of Makasssar - Burhanuddin, Burhanuddin; Chusaemah, Chusaemah (International Journal of Halal System and Sustainability https://jurnal.narotama.ac.id/https://www.spb.gba.gov.ar/campus/https://conference.trunojoyo.ac.id/https://ojs.ucp.edu.ar/https://libros.cimsur.unam.mx/https://ojs.stikesmucis.ac.id/http://medi, 2023)
Halal industry no longer applies to solely food production and consumption, but also evolved holistic halal concept that encompasses various commercial activities. Halal tourism is now fast becoming a new phenomenon in the general tourism, south Sulawesi’s government had tried to socialize the halal food tourism, Makassar is the main city of the socialization in three recent years that encouraged the writers to find out the effects of tourists visit . The writers had tried to get more information of the effects of tourist visit after the socialization, both for domestic and international tourists. The writers used purposive Sampling and had interviewed those who worked for tourism sectors in South Sulawesi province to find out the effects of the visit. The results of the writing were; there would be the positive effect from the Muslim tourists (80%), especially the local, domestic, and Malaysian, and bad or negative effect to the most of western tourists in the hospitality industry (0,15%), and there wouldn’t be any market segment at all (0,05%). The government should have the sustainable socialization, tied policy, and build the supported infrastructures in tourist destination ares like; International airport, harbor, good roads, and collaborate with the food industries.